Pengaruh Keungulan Produk Tabungan Mudharabah terhadap Kepuasan Nasabah di BSI Cabang Tuban - A’yun, Inarotul; Faizah, Rifatin; Fatimah, Siti (Program Studi Perbankan Syariah STAI Senori Tuban, 2023)
This journal discusses the advantages of mudharabah savings products on customer satisfaction at the BSI Tuban branch. The purpose of this research is to measure the influence of the superiority of mudharabah savings products at the BSI Tuban branch. This research uses a quantitative type of research. The population of this study were customers from the Tuban branch of BSI bank. The data collection technique in this research is by distributing questionnaires to customers for answers. and the data management technique in this research is to use quantitative data analysis using SPSS. Next, a classic assumption test will be carried out consisting of a normality test and a heteroscedasticity test. Next, use linear regression analysis, and hypothesis testing, t-test, coefficient of determination. The results of this research state that the superiority of mudharabah savings products has a positive effect on customer satisfaction. The research was conducted with 100 respondents from customers or service users of the Bank BSI Tuban branch. Based on data obtained from distributing questionnaires, the T-test results were 1.233 with T table 1.66023, meaning T count < T table, with a significant value of 0.228, it can be concluded that there is a significant influence on customer satisfaction.